Development of Physics Learning Multimedia with Tutorial Model Based on Local Wisdom ‘Tebing Gerinting’ for Middle School - Linda Lia; Sugiarti (Department of Physics Education, Universitas Mataram, 2022)
The research is aims to develop a physics learning multimedia with tutorial model based on the local wisdom of Tebing Gerinting in junior high schools which is valid, practical, and has potential effects. This type of research uses development research from Akker with Rowntree model which consists of planning, development, and evaluation. Tessmer's formative assessment is the one that is being used in this research. Data was collected by documentation, walkthroughs, interviews, questionnaires and tests. From the conclusions of the review by experts, it was obtained an average of 0.93 in the very valid category. From the one-to-one results, an average of 1 is in the very practical category. At the small group stage, 3.48 on averages, with a very practical category, was discovered. Field trials showed an average N-Gain percentage of 56.17%, which fits into the category of fairly effective results. Therefore, it can be concluded that the learning physics multimedia with tutorial model based on the local wisdom of Tebing Gerinting is very valid, very practical, and has a potential effect on learning outcomes. The average percentage of N-Gain, which is at a fairly effective level, and the improvement in student learning outcomes are two examples of the potential effect that show how successfully the multimedia products generated are used in learning.